Near-0 °C surface temperature and precipitation type patterns across Canada - Mekis, Eva; Stewart, Ronald E.; Theriault, Julie M.; Kochtubajda, Bohdan; Bonsal, Barrie R.; Liu, Zhuo (Hydrology and Earth System Sciences, 2020)
Abstract. The 0 ∘C temperature threshold is critical for many meteorological and hydrological processes driven by melting and freezing in the atmosphere, surface, and sub-surface and by the associated precipitation varying between rain, freezing rain, wet snow, and snow. This threshold is especially important in cold regions such as Canada, because it is linked with freeze–thaw, snowmelt, and permafrost. This study develops a Canada-wide perspective on near-0 ∘C conditions using hourly surface temperature and precipitation type observations from 92 climate stations for the period from 1981 to 2011. In addition, nine stations from various climatic regions are selected for further analysis. Near-0 ∘C conditions are defined as periods when the surface temperature is between −2 and 2 ∘C. Near-0 ∘C conditions occur often across all regions of the country, although the annual number of days and hours and the duration of these events varies dramatically. Various types of precipitation (e.g., rain, freezing rain, wet snow, and ice pellets) sometimes occur with these temperatures. Near-0 ∘C conditions and the reported precipitation type occurrences tend to be higher in Atlantic Canada, although high values also occur in other regions. Trends of most temperature-based and precipitation-based indicators show little or no change despite a systematic warming in annual surface temperatures over Canada. Over the annual cycle, near-0 ∘C temperatures and precipitation often exhibit a pattern: short durations occur around summer, driven by the diurnal cycle, and a tendency toward longer durations around winter, associated with storms. There is also a tendency for near-0 ∘C surface temperatures to occur more often than expected relative to other temperature windows at some stations due, at least in part, to diabatic cooling and heating that take place with melting and freezing, respectively, in the atmosphere and at the surface.

Meteorological observations and measurements collected during the Storms and Precipitation Across the continental Divide Experiment (SPADE), April – June 2019 - Thériault, Julie M.; Déry, Stephen J.; Pomeroy, John; Stewart, Ronald E.; Smith, Hilary; Thompson, Hadleigh; Bertoncini, André; Desroches-Lapointe, Aurélie; Hébert-Pinard, Charlie; Mitchell, Selina; Morris, Jeremy; Almonte, Juris; et al. (Federated Research Data Repository / dépôt fédéré de données de recherche, 2020)
Global Water Future’s Storms and Precipitation Across the continental Divide Experiment (SPADE) was initiated to enhance our knowledge of the contribution of different moisture flows on precipitation across the Canadian Rockies. SPADE installed instrumentation on both sides of the continental divide to gather automated and manual observations during an intensive field campaign from 24 April to 26 June 2019. Various meteorological instruments were deployed including a two Doppler LiDARs, three vertically pointing micro rain radars and three optical disdrometers, alongside human observers during precipitation events. Detailed meteorological data such as air temperature, relative humidity, 3D wind fields, vertical profiles of radar reflectivity and Doppler velocity, precipitation and its type, and snow microphotography images were collected. This dataset will serve as a baseline for future work on atmospheric conditions over major orographic features by comparing the varying conditions on either side of a large topographic feature.
Keywords: Canadian Rockies; Hydrometeorology; Meteorology and weather; Météorologie et temps; atmospheric sciences; continental divide; meteorology; precipitation